2020
DOI: 10.3390/cancers12123822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on Lungs: Focusing on Prospective Malignant Phenotypes

Abstract: Currently, the healthcare management systems are shattered throughout the world, even in the developed nations due to the COVID-19 viral outbreak. A substantial number of patients infected with SARS-CoV2 develop acute respiratory distress syndrome (ARDS) and need advanced healthcare facilities, including invasive mechanical ventilation. Intracellular infiltration of the SARS-CoV2 virus particles into the epithelial cells in lungs are facilitated by the spike glycoprotein (S Protein) on the outer side of the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 122 publications
2
42
0
1
Order By: Relevance
“…The second major finding of this study is that the different CCTAs and lowered SpO2% were significantly associated with the appearance of the physio-affective core as well as with melancholia, cognitive symptoms and insomnia. Many (up to 70%) RT-PCR test positive COVID-19 patients show CCTAs (Adams et al, 2020), which indicate lung inflammation, bronchiolitis, pneumonia and lung fibrosis (Sadhukhan et al, 2020). In our study, the presence of CCTAs is strongly associated with lowered SpO2 indicating that pneumonia and lung lesions may cause decreased peripheral oxygen saturation, which is often decreased in COVID-19 patients and especially in those with more severe illness (Dai et al, 2020;Luks and Swenson, 2020).…”
Section: Effects Of Pneumonia On Affective and Physiosomatic Symptomssupporting
confidence: 46%
See 1 more Smart Citation
“…The second major finding of this study is that the different CCTAs and lowered SpO2% were significantly associated with the appearance of the physio-affective core as well as with melancholia, cognitive symptoms and insomnia. Many (up to 70%) RT-PCR test positive COVID-19 patients show CCTAs (Adams et al, 2020), which indicate lung inflammation, bronchiolitis, pneumonia and lung fibrosis (Sadhukhan et al, 2020). In our study, the presence of CCTAs is strongly associated with lowered SpO2 indicating that pneumonia and lung lesions may cause decreased peripheral oxygen saturation, which is often decreased in COVID-19 patients and especially in those with more severe illness (Dai et al, 2020;Luks and Swenson, 2020).…”
Section: Effects Of Pneumonia On Affective and Physiosomatic Symptomssupporting
confidence: 46%
“…Importantly, our PLS analysis showed that one common "infection-immune-inflammatory core" underpins pneumonia-associated lung lesions, lowered SpO2 and immune activation, and that this core explains 70% of the variance in the physio-somatic core, and a relevant part of the variance in melancholia (31.1%), insomnia (30% when shared with BMI) and neurocognitive impairments (8.8%). As such, we may conclude that acute SARS-CoV-2 infection is often accompanied by lung lesions and lowered SpO2 which both are known to induce immune-inflammatory pathways (Sadhukhan et al, 2020) and that the increased incidence of neuro-psychiatric symptoms in COVID-19 should be attributed at least in part to the infection-immune-inflammatory core of COVID-19. Moreover, SARS-CoV-2 can infect the brain, causing neuroinflammation and this is believed to be a another source of neuropsychiatric symptoms including chronic fatigue after recovery (Mandal et al, 2021).…”
Section: Effects Of Pneumonia On Affective and Physiosomatic Symptomsmentioning
confidence: 94%
“…In this respect, the similarity and overlap in CT features between the COVID-19 illness and lung cancer progression has been highlighted and the widespread GGO indings in CT images of COVID-19 patients have raised the probability of developing lung cancer in due course. Thus, a follow up at regular interval is in long Covid patients [16].…”
Section: Host Immune System and Sars-cov2 Infectionmentioning
confidence: 99%
“…The SARS-CoV-2 Infection causes molecular changes and recruitment of in lammatory cytokines/chemokines in lung tissue microenvironment [16]. As well known, several proin lammatory cytokines are involved in lammation-associated neoplastic alterations through various molecular and metabolic pathways, and ROS.…”
Section: Covid-19 Follow Up: Links With Neoplastic Lesionsmentioning
confidence: 99%
“…The widespread GGO findings in CT images of COVID-19 patients have raised the probability of developing lung cancer. Thus, there is a need for follow up at regular interval for early detection of any kind of pre-neoplastic lesions [16].…”
Section: Host Immune System and Sars-cov2 Infectionmentioning
confidence: 99%